NK Cell-Based Cancer Immunotherapy - Susana Larrucea (Frontiers Research Topics, 2016)
Natural killer (NK) cells are innate lymphoid cells that have a significant role in regulating the defenses against cancer development and certain viral infections. They are equipped with an array of activating and inhibitory receptors that stimulate or diminish NK cell activity, respectively. Inhibitory receptors include, among others, the MHC class I ligands killer cell immunoglobulin-like receptors (KIR) in humans, and members of the Ly49 family of receptors in mice, and CD94/NKG2A. Activating receptors include cytokine and chemokine receptors, and those that interact with ligands expressed on target cells, such as the natural cytotoxicity receptors or NCRs (NKp30, NKp44 and NKp46), NKG2D, CD244 and DNAM-1. In addition, NK cells express Fc?RIIIA or CD16, the receptor that exerts antibody-dependent cell mediated cytotoxicity (ADCC). NK cells also express the death ligands FasL and TRAIL. The killing or sparing of target cells depends on the integration of distinct signals that originate from NK cell receptors. NK cells spare healthy cells that express normal levels of MHC class I molecules and low amounts of stress-induced self-molecules, whereas they kill target cells that down-regulate MHC class I molecules and/or up-regulate stress-induced self-molecules. The latter are common signatures of virus-infected cells and tumors. All the accumulated knowledge on NK cell biology, along with many clinical observations, is driving multiple efforts to improve the arsenal of NK cell-based therapeutic tools in the fight against malignant diseases. Indeed, NK cell-based immunotherapy is becoming a promising approach for the treatment of many cancers. It is well known that NK cells have a significant role in the anti-tumor effect of therapeutic antibodies that use ADCC as a mechanism of action. In addition to this, administration of autologous and allogeneic NK cells after activation and expansion ex vivo is used in the treatment of cancer. Moreover, adoptive transfer of NK cell lines has been tested in humans, and genetically modified NK cells expressing chimeric antigen receptors are being studied in preclinical models for potential use in the clinic.